Communications in Partial Differential Equations - Communications in Partial Differential Equations (Taylor & Francis, 2026)
This journal aims to publish high quality papers concerning any theoretical aspect of partial differential equations, as well as its applications to other areas of mathematics. Suitability of any paper is at the discretion of the editors. We seek to present the most significant advances in this central field to a wide readership which includes researchers and graduate students in mathematics and the more mathematical aspects of physics and engineering.
FI 1.28
Q1
Keywords: Mathematics & Statistics; Matemáticas; Ingeniería; Acuerdos transformativos; Transformative agreements; Física; Ecuaciones diferenciales parciales; Biología cuántica